Strategies to improve healthcare services for patients with sickle cell disease in Nigeria: The perspectives of stakeholders - Isa, Hezekiah; Okocha, Emmanuel; Adegoke, Samuel Ademola; Nnebe-Agumadu, Uche; Kuliya-Gwarzo, Aisha; Sopekan, Alayo; Ofakunrin, Akinyemi Olugbenga; Ugwu, Ngozi; Hassan, Abdul-Aziz; Ohiaeri, Chinatu; Madu, Anazoeze; Diaku-Akinwumi, Ijeoma; et al. (Frontiers in Genetics, 2023)
Background: Sickle cell disease (SCD) continues to pose physical and psychosocial burdens to patients, caregivers and health workers. Stakeholder engagement in the processes of policy making and implementation is increasingly becoming the cornerstone of best practices in health care. Aim and Objectives: To engage stakeholders with a view to assessing the knowledge of SCD; ascertain the challenges associated with accessibility and affordability of healthcare services; improve the quality of care, and thereby effect behavioral change through increasing attendance and follow-up of patients in the clinics. Methodology: A Stakeholders’ Engagement meeting organized by the Sickle Pan Africa Research Consortium Nigeria Network (SPARC-NEt) was attended by patients, caregivers and members of patient support groups, healthcare providers and management/policymakers. The engagement was through PowerPoint presentations, structured questionnaires and an interactive session. The structured questionnaire assessed the knowledge of stakeholders about SCD; the quality of healthcare services; challenges with access and affordability; and SCD-related government policies. Results: Three hundred and twelve stakeholders attended the engagement meeting. Of the 133 that participated in the study, medical workers were the most represented. The majority had good knowledge of what causes SCD (96.2%) and the best place to get help during SCD crisis (98.5%). However, knowledge of the specific preventive measures of SCD and its crisis was not optimal. In terms of the role of community engagement and education, only about one-quarter of the study participants, 34 (25.6%) knew about their positive role in reducing the prevalence of SCD and alleviating SCD crises. Challenges identified include inadequate healthcare personnel and facilities, delay in obtaining laboratory results, long waiting time in the clinic, poor communication, absence of holistic consultation, uncoordinated health care services, high cost of care, ignorance, non-prioritization of SCD by government, lack of multisectoral collaboration and partnership with NGOs and international organizations. Strategies proffered to improve healthcare services include, community/stakeholder engagement and health education, sickle cell daycare services, access to a willing and dedicated multidisciplinary workforce, collaboration with support groups and government policies and programs. Conclusion. There is need for regular stakeholder engagement to improve access to health care services for SCD patients in Nigeria